The Effect of Contextual Teaching and Learning Combined with Peer Tutoring towards Learning Achievement on Human Digestive System Concept - Abadiyah, Farhah; Juanengsih, Nengsih; Fadlilah, Dina Rahma (Jurnal Penelitian dan Pembelajaran IPA, 2017)
Abstract This research aims to know the influence of contextual teaching and learning (CTL) combined with peer tutoring toward learning achievement on human digestive system concept. This research was conducted at one of State Senior High School in South Tangerang in the academic year of 2016/2017. The research method was quasi experiment with nonequivalent pretest-postest control group design. The sample was taken by simple random sampling. The total of the sampels were 86 students which consisted of 44 students as a controlled group and 42 students as an experimental group. The research instrument was objective test which consisted of 25 multiple choice items of each pretest and posttest. The research also used observation sheets for teacher and students activity. The result of data analysis using t-test on the two groups show that the value of tcount was 2.40 and ttable was 1.99 on significant level α = 0,05, so that tcount > ttable.. This result indicated that there was influence of contextual teaching and learning (CTL) combined with peer tutoring toward learning achievement on human digestive system concept.Keywords: Contextual Teaching and Learning, Peer Tutoring, Learning Achievement, Human Digestive System